Distance between occupations in the task complexity space - Ian Nicole Generalao (University of the Philippines, School of Economics (UPSE), 2020)
Using the task-based framework, this study measures the level of skill transferability across occupations by building an occupational distance measure. The distance measure allows us to compare occupations in terms of their task profiles. Skill transferability between two occupations is high if the occupations are "close" with each other and low if occupations are "far" from each. In addition, the distance measure allows us to classify which occupational moves are considered an upskilling, down-skilling or lateral occupational moves. The occupational distance measure is also applied to the sample of TVET graduates to measure their level of occupational mobility pre- and post-training. This has important implications in terms of the amount of additional training and education needed by individuals to move from one occupation to another. This study constitutes a basis for further studies on understanding the relationship among occupational distances, mobility and wage differentials in different economies.
Keywords: J24; J62; 330; Tasks; Skills; Human Capital; Occupational Mobility